2001
DOI: 10.1002/jso.1090
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers in Paget disease of the breast

Abstract: Tumors from patients with Paget disease of the breast were positive for c-erbB-2, Cyclin D1, and Ki-67, molecular markers commonly associated with more aggressive tumor behavior and poorer survival in breast cancer patients. Few of these tumors expressed Bcl-2 or ER and PR, which are generally associated with a better prognosis. Similar expression of these markers in both Paget cells and the underlying carcinoma supports the theory that these cells are the result of an intraepidermal spread of ductal carcinoma. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 38 publications
5
43
0
4
Order By: Relevance
“…The prognosis of these patients depends on the presence of lump and associated lymph node metastases. They have found that overall survival correlates with lymph node status, with node-negative patients having a survival of 75-95 % whereas in node-positive patients, it was 20-25 % [6,23].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of these patients depends on the presence of lump and associated lymph node metastases. They have found that overall survival correlates with lymph node status, with node-negative patients having a survival of 75-95 % whereas in node-positive patients, it was 20-25 % [6,23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one study, only one of 73 grade I IDC cases and one of 67 low-grade classic ILC cases showed HER-2 amplification detected by FISH [86]. HER-2 overexpression and HER-2 amplification have been a consistent feature of both mammary and extramammary Paget's disease [124,125] (Fig. 2).…”
Section: Her-2 Expression and Breast Pathologymentioning
confidence: 99%
“…Only 1 of 73 grade I invasive ductal carcinomas and 1 of 67 classic lobular carcinomas showed amplification of the HER-2/neu gene. HER-2/neu overexpression has been a consistent feature of both mammary and extramammary Paget's disease [173,174]. The majority of studies that have compared HER-2/neu status in paired primary and metastatic tumor tissues have found an overwhelming consistency of the patient's status regardless of the method of testing (IHC versus FISH) [175][176][177][178][179][180].…”
Section: Her-2/neu Expression and Breast Pathologymentioning
confidence: 99%